Pengaruh Kadar Lempung Dengan Kadar Air Di Atas OMC Terhadap Nilai CBR Dengan Dan Tanpa Rendaman Pada Tanah Lempung Organik - Khairatu Zaro; Soewignjo Agus Nugroho; Ferry Fatnanta (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Strength and durability of road pavement depend on engineering properties of subgrade. However, soils used as subgrade may not satisfy the required quality. Peat or organic soils is not to advantage of construction because bearing capacity or value of peat soil’s CBR is low. This paper intends to find out more about CBR value of organic soils on OMC and saturated condition . This research investigated the changes of CBR value with moisture content in the range of OMC to saturated. And influenced percentage varied of peat in mixture organic soils (clay and peat). The result of this study showed that for increasing of peat content reduce  CBR values at OMC condition. CBR value  in addition 10% of peat decreased CBR significantly  to 2,88 %  as compared  to original soil (clay) is about 23,88%.  And when compaction of soils with water content above OMC,  incresing content of water reduce  value of CBR.  Key Words: CBR, water content, peat